(untitled) (Research, Society and Development, 2022)
Leprosy is an infectious disease that requires continued care for its complete cure. Patients with this and other chronic diseases presented barriers in the longitudinality of treatment with the new coronavirus pandemic. The aim of this article was to assess the impact of the COVID-19 pandemic on the continued care of Hansen’s disease. This is an exploratory-descriptive integrative review that researched the keywords “Leprosy”, “Continued Care” and “COVID-19” connected by the term AND in the Latin American and Caribbean Literature on Health Sciences databases (LILACS), Online System of Search and Analysis of Medical Literature (MEDLINE) and Online Scientific Electronic Library (SCIELO) through the Virtual Health Library (BVS). 55 articles were found, of which, when filtered by inclusion and exclusion criteria, 07 studies were chosen for the final preparation of this document. The results showed that there was underreporting of leprosy cases during the COVID-19 crisis due to barriers to accessing health services, in addition to neglecting basic aspects of the continued treatment of Hansen’s disease, namely: lack of availability of medicines , awareness campaigns and training courses. It is concluded that government sectors need to develop plans to maintain adequate care for leprosy even in pandemic situations, as the disease generates high morbidity in these patients, who need attention and comprehensiveness to resolve this chronic infection.